PUBLIC CONSULTATIONS AS AN INSTRUMENT OF CIVIL SOCIETY' INFLUENCE ON POLICY FORMING - Біденко, Ю. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
In the article the purposes of the public consultations and their place among the different forms of citizens involvement  in the political decision-making process are analyzed. An observation  of general principles and practices stated in domestic and international documents (i.e. in the acts, codes, and recommendations of EU, Council of Europe, and OSCE) is provided. The author suggests a classification of consultation instruments due to the public policy phase and considers the arguments on the necessity to unify these instruments and to consolidate them by special law in contemporary Ukraine.